Developing Highly Porous Glass Microspheres via a Single-Stage Flame Spheroidisation Process. Issue 1 (1st June 2022) - Nuzulia, N A; Islam, T; Saputra, A; Sudiro, T; Timuda, G E; Mart, T; Sari, Y W; Ahmed, I
Abstract: Glass microspheres are gaining attention in bone tissue engineering due to their ability to convert into hydroxyapatite-like materials, resembling the inorganic mineral of natural bone. The morphology of glass microspheres as starting material has been considered to influence the conversion rate and the resulting product where porous microspheres could promote faster conversion to hydroxyapatite than solid microspheres. This paper reports on manufacturing glass microspheres (solid and porous) using a flame spheroidisation process. The effect of various gas ratios of acetylene and oxygen on the morphological changes of glass microspheres was investigated. Irregular shaped glass particles with starting particle size ranges of 63 – 125 μm were used as feed and delivered to a hot flame to produce solid microspheres. To manufacture porous glass microspheres via a single-stage flame spheroidisation process, calcium carbonate was utilised as a porogen and mixed with the glass particles. Solid and porous glass microspheres were successfully produced, exploring various gas ratios of 3:3, 4:7, 5:7 and 6:7 with a mean particle size range between 73 – 105 μm. Moreover, the average pore size of 6 μm and 9 μm was obtained using 5:7 and 6:7 gas ratios, respectively. This single-stage flame spheroidisation process is a promising method for producing both solid and porous bioactive glass microspheres.